2014
DOI: 10.3168/jds.2014-7898
|View full text |Cite
|
Sign up to set email alerts
|

Age at calving in heifers and level of milk production during gestation in cows are associated with the birth size of Holstein calves

Abstract: The objective of the present study was to evaluate environmental and dam factors associated with birth size of Holstein calves. Data of 1,594 births from dairy herds in Belgium and Germany were analyzed in a retrospective cross-sectional study. Immediately after birth, the birth weight of the calves was measured. On the next day, the heart girth (HG), withers height, and diagonal length of the dams and calves were measured. Parity, body condition score, gestation length (GL), and age at calving were recorded f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
44
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 42 publications
8
44
1
2
Order By: Relevance
“…However, the prevalence of dystocia and stillbirth remain unacceptably high, and inappropriate sire selection seems to be a big part of the problem. Contrary to results from Kamal et al (2014), AGE of heifers and DIM of multiparous cows at conception were not related to CBW. Moreover, there was no significant effect of AGE or DIM on GL or dystocia.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…However, the prevalence of dystocia and stillbirth remain unacceptably high, and inappropriate sire selection seems to be a big part of the problem. Contrary to results from Kamal et al (2014), AGE of heifers and DIM of multiparous cows at conception were not related to CBW. Moreover, there was no significant effect of AGE or DIM on GL or dystocia.…”
Section: Discussioncontrasting
confidence: 52%
“…Indeed, age at first parturition (AGE) and milk production during gestation of lactating dairy cows have recently been associated with CBW (Kamal et al 2014), probably due to energy partitioning between growth (heifers), and intrauterine growth of the fetus. However, the effect of days in milk at conception on calvingrelated disorders is unknown (Ingvartsen et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…These results correspond with the research of Kamal et al (2014), who found age at first calving in HF heifers and milk yield in HF cows to be better predictors of calf size than body measurements. The latter implies that, although larger dams are believed to have a larger uterus (Allen et al, 2002) and a higher feed intake, the fetus is not directly benefitting from this advantage, which suggests other maternal tissues to have a higher priority in terms of nutrient partitioning.…”
Section: Discussionsupporting
confidence: 91%
“…The former implies that gestation in primiparous animals should take place when dams are still growing, while the latter implies that in multiparous animals, gestation should to a large extent coincide with lactation. Recently, we have demonstrated that young age at first gestation and a high level of milk yield during gestation in multiparous dams both reduce intrauterine foetal development, probably by diverting a significant proportion of nutrients to dam growth and milk production (Kamal et al., ). Subsequently, we have demonstrated that both growth and lactation during gestation have a significant impact on gross placental morphology in cattle (Van Eetvelde et al., ).…”
Section: Introductionmentioning
confidence: 99%